2013
DOI: 10.1097/aud.0b013e3182611982
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Input Processing and Type of Personal Frequency Modulation System on Speech-Recognition Performance of Adults With Cochlear Implants

Abstract: Speech recognition in noise is substantially affected by the type of sound processor, FM system, and implementation of ASC used by a Cochlear implant recipient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
1
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 20 publications
2
32
1
2
Order By: Relevance
“…Many persons with cochlear implants understand speech in face-to-face conversations in quiet (1,2), but experience poorer hearing performance in more challenging listening situations, such as hearing speech in noise (3)(4)(5)(6) and communicating by mobile telephones. Cochlear implant manufacturers provide several technologies to improve performance in noise.…”
mentioning
confidence: 99%
“…Many persons with cochlear implants understand speech in face-to-face conversations in quiet (1,2), but experience poorer hearing performance in more challenging listening situations, such as hearing speech in noise (3)(4)(5)(6) and communicating by mobile telephones. Cochlear implant manufacturers provide several technologies to improve performance in noise.…”
mentioning
confidence: 99%
“…Researchers have conclusively shown that both types of systems provide a significant improvement in speech recognition in noise compared with use of a CI alone. 18,20,21 However, the comparison of performance with induction neckloop with directly coupled systems led to mixed results. Schafer and colleagues evaluated speech recognition in noise of nine CI recipients using the Oticon Arc (Copenhagen, Denmark) induction neckloop and the Oticon R2 directly coupled receiver in Advanced Bionics (Valencia, CA), Cochlear Ltd. (Cochlear, Sydney, Australia), and MED-EL (Innsbruck, Austria) implant users.…”
Section: Remote Microphone Rf Technologies Used With Cismentioning
confidence: 99%
“…22 In contrast, Wolfe and colleagues evaluated speech recognition in noise for 15 subjects who used Nucleus Freedom or Nucleus 5 (Sydney, Australia) CIs. 21 Performance was evaluated with both the Freedom and Nucleus 5 sound processors coupled to each of two types of personal remote microphone systems: (1) the Phonak MyLinkþ (Murten, Switzerland) induction neckloop system, and (2) a Phonak directly coupled receiver (the Freedom Micro-Link for the Freedom sound processor and the Phonak MLxS for the Nucleus 5 sound processor). For the subjects who used the Freedom sound processor, Wolfe et al reported significantly poorer speech recognition with use of the induction neckloop system relative to the directly coupled system by an average of 25 and 39% at a competing noise level of 65 decibels Aweighted (dBA) and 75 dBA, respectively.…”
Section: Remote Microphone Rf Technologies Used With Cismentioning
confidence: 99%
“…Los sistemas FM son bastante utilizados por las personas con discapacidad auditiva (Chisolm, Noe, Mcardle and Abram, 2008) y entre sus resultados encontramos una mejora en la participación en diferentes contextos como el educativo (Jacob et al, 2014), además de una mejora en el reconocimiento de habla (Wolfe et al, 2013). Existen algunos estudios experimentales sobre la eficacia del equipo FM y sus medidas de resultados (Boothroyd, 2004;Lewis, Crandell, Valente & Enrietto, 2004;Lewis, Valente, Horn & Crandall, 2005).…”
Section: Equipos De Frecuencia Modulada (Fm)unclassified